Morphological, immunohistochemical and molecular study of renal lesions in canine visceral leishmaniasis (CVL) - Ferrari, Heitor Flavio; Carreira, Vinícius Soares; Moreira, Márcio Anontio Batistela; Matta, Vania Ribeiro da; Haga, Claudio Hiroyassu; Luvizotto, Maria Cecília Rui [UNESP] (My University, 2010)
Canine visceral leishmaniasis (CVL) is an anthropozoonosis characterized by a clinically chronic progressive disease. Non lymphoid organs are also affected, especially the kidneys. Dogs with leishmaniasis usually die with renal failure despite treatment. Haematoxylin-eosin (HE) staining in kidney tissue sections has low sensitivity for parasite identification. Immunohistochemistry (IHC) and polymerase chain reaction (PCR) are efficient methods for Leishmania sp. antigen and DNA detection in cases of low parasite burden. The present study aims to identify renal lesions of CVL and correlate them with microscopic findings determined by histochemistry, IHC and PCR. Both IHC and PCR provided similar positivity for amastigote identification, 3/20 animals (15%), thus increasing detection of the parasite in renal tissues when compared with histopathologic examination. The lesion most commonly observed with visceral leishmaniasis-positive canine kidney tissue was membranoproliferative glomerulonephritis, followed by interstitial nephritis without correlation to the number of amastigotes.

La leishmaniosis visceral canina (CVL) es una antropozoonosis caracterizada por evolución crónica y progresiva. Órganos no pertenecientes al sistema linfático también son afectados, destacándose los riñones. Perros con leishmaniosis desarrolan lesión renal crónica, que evoluye al óbito, aún después del tratamiento. La identificación del parásito en la tejido renal, corado con hematoxilina y eosina (HE), presenta baja sensibilidad. Las técnicas de inmunoistoquímica (IHC) y de Reacción en Cadena por la Polimerase (PCR) son eficientes en la detección del antígeno y del DNA de la Leishmania sp en los casos de bajo parasitismo. El presente trabajo tuvo como objetivos identificar las alteraciones renales decurrentes de la CVL y asociar con lesiones histológicas observadas en las coloraciones de histoquímica, IHC y PCR. El análisis de la IHC y PCR revelaron positividad semejante en la detección amastigotas, 3/20 animales (15%), lo que muestra el parásito en el tejido renal, cuando comparado con el examen histopatológico HE. En los casos de leishmaniosis visceral con exhibición en de amastigotas en el tejido renal, las lesiones microscópicas predominantes fueron glomerulonefritis membranoproliferativa y nefritis intersticial, no correlacionada con número de amastigotas.
Studio morfológico, inmunoistoquímico y molecular en riñones de perros portadores de leishmaniosis visceral
Keywords: Dog; Visceral leishmaniasis; Kidney; Immunohistochemistry; Polymerase chain reaction; Perro; Leishmaniosis visceral; Riñones; Inmunoistoquímica; Reacción en Cadena por la Polimerase (PCR)